Clinical and mutational spectrum of paediatric Charcot-Marie-Tooth disease in a large cohort of Chinese patients - Ma, Yan; Duan, Xiaohui; Liu, Xiaoxuan; Fan, Dongsheng (Frontiers in Genetics, 2023)
Background: Charcot-Marie-Tooth disease (CMT) is the most common inherited neurological disorder suffered in childhood. To date, the disease features have not been extensively characterized in the Chinese paediatric population. In this study, we aimed to analyse the clinical profiles and genetic distributions of a paediatric CMT cohort in China. Methods: A total of 181 paediatric CMT patients were enrolled. After preexcluding PMP22 duplication/deletion by multiplex ligation-dependent probe amplification (MLPA), Sanger sequencing, targeted next-generation sequencing (NGS) or whole-exome sequencing (WES) was performed to obtain a genetic diagnosis. Detailed information was collected to explore the spectrum of subtypes and genotype-phenotype correlations. Results: Pathogenic mutations were identified in 68% of patients in this study; with PMP22 duplication, MFN2 and GJB1 were the most frequent disease-causing genes. Of note, respect to the higher prevalence worldwide, CMT1A (18.2%) was relatively lower in our cohort. Besides, the mean age at onset (8.3±5.7 years) was significantly older in our series. In genotype-phenotype analyse, PMP22 point mutations were considered the most severe genotypes and were mostly de novo. In addition, the de novo mutations were identified in up to 12.7% of all patients, which was higher than that in other studies. Conclusion: We identified a relatively lower detection rate of PMP22 duplication and a higher frequency of de novo variants among paediatric patients in China. We also identified the genetic and phenotypic heterogeneity of this cohort, which may provide clues for clinicians in directing genetic testing strategies for Chinese patients with early-onset CMT.